Response Surface Modelling of the Mechanical Properties of Oil Palm Empty Fruit Bunch Fibre Reinforced Polyester Composites - Chinwe Evangeline Kamma (Universitas Sanata Dharma, 2022)
This work presents a systematic approach to evaluate and study the effect of fibre aspect ratio and fibre volume fraction on the tensile strength, ultimate elongation, modulus of elasticity, strength and impact energy of oil palm empty fruit bunch fibre reinforced polyester composites. Hand-lay-up technique was used in the fabrication of the composite materials. Response surface methodology was used to study the effect of the selected factors on the mechanical properties of oil palm empty fruit bunch fibre reinforced polymer-based composite. The optimum fibre aspect ratio and fibre volume fraction for each mechanical property was determined. From the result of optimization, the maximum value for tensile strength obtained was 12.15MPa at a fibre aspect ratio of 64 and fibre volume fraction of 26%. The maximum value for ultimate elongation was obtained as 1.939% at a fibre aspect ratio of 124 and fibre volume fraction of 50%, the maximum value for modulus of elasticity was obtained as 1509 MPa at a fibre aspect ratio of 124 and 34% volume fraction. The maximum value for toughness was obtained as 0.1231MPa at a fibre aspect ratio of 89 and a volume fraction of 30%. The maximum value of impact energy was obtained as 5.765 ft/lbs at 28% fibre volume fraction and an aspect ratio of 69. The maximum value of impact strength was obtained as 4.574N/cm3 at a 36% volume fraction and an aspect ratio of 64.